Loyalitas Pasien Rawat Inap Melalui Layanan BPJS Kesehatan (Studi pada RSI Jemursari Surabaya) - Putri Mahanani; Denis Fidita Karya (UNUSA Press, 2016)
BPJS is one of the health services provided by the government to the people ofIndonesia. In the process of patient care by using BPJS there were some complaints fromconsumers related to the quality of service. Poor service quality will have an impact onconsumer dissatisfaction in the service, so that it is capable of influencing consumer loyalty.Loyalty can only be generated if consumers have experienced the satisfaction of a goodservice quality provided by the service provider. This study aims to determine the effectof service quality on customer loyalty. In this case the customer satisfaction are thingsthat need to be met first before consumers get to the stage of loyalty. Respondents of thisstudy are inpatients in RSI Jemursari Surabaya as many as 100 people who use the serviceBPJS third grade. This study used survey method and analyzed using path analysis withPartial Least Square (PLS). Results from this study is the quality of service has an influenceon loyalty with mediation of consumer satisfaction. Loyalty can occur if the satisfactionfelt by consumers. Thus, in this study, customer satisfaction a mediating variable for therelationship between the variables of service quality and customer loyalty.